2020
DOI: 10.47009/ajcpn.2020.8.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Urine Uric Acid Creatinine Ratio as a Diagnostic and Prognostic Marker of Neonatal Birth Asphyxia

Abstract: Background: Cerebral hypoxia can result in anaerobic glycolysis which leads to decreased phosphorylase production and increased uric acid which gets excreted in the urine where it can be easily detected. The aim of the study is to assess the utility of urine uric acid creatinine ratio (UA/Cr) as an additional marker of neonatal depression and birth asphyxia and its utility as a potential prognostic indicator for the immediate outcome. Subjects and Methods: It was a case-control study that included 30 newborns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Our study showed a significant higher ratio of UUA/ Cr in premature neonates admitted in NICU suffering hypoxia. Several other studies have reached similar results [2,3,6,8,9,[13][14][15][16][17][18][19][20][21]. In the case -control study of Sreekrishna et al on 50 normal neonates and 50 newborn infant with asphyxia, the mean Urinary Uric Acid / Cr ratio in case and control group was 2.8 ± 0.9 and 0.8 ± 0.2 respectively which shows a significant higher ratio in case group (P < 0.001) [2].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our study showed a significant higher ratio of UUA/ Cr in premature neonates admitted in NICU suffering hypoxia. Several other studies have reached similar results [2,3,6,8,9,[13][14][15][16][17][18][19][20][21]. In the case -control study of Sreekrishna et al on 50 normal neonates and 50 newborn infant with asphyxia, the mean Urinary Uric Acid / Cr ratio in case and control group was 2.8 ± 0.9 and 0.8 ± 0.2 respectively which shows a significant higher ratio in case group (P < 0.001) [2].…”
Section: Discussionsupporting
confidence: 64%
“…In recent years, some studies have shown that The UUA/Cr ratio may be used as an additional marker for perinatal asphyxia in full-term and preterm infants. Within 24 h of birth, UUA/Cr ratio is a simple, fast, and inexpensive way to diagnose hypoxic episodes of NICU admitted patients compared with other markers such as xanthine, hypoxanthine and ascorbic acid [5][6][7][8][9]. The Urinary Uric Acid / Cr ratio, as a biochemical marker, can support the clinical diagnosis and severity of asphyxia previously determined by the Apgar score.…”
Section: Introductionmentioning
confidence: 99%